Transmittance investigation on capacitive mesh on thick dielectric substrates as output windows for optically pumped terahertz lasers - 祁春超 左都罗 卢彦兆 唐建 程祖海 (Chinese physics B, 2010)
This paper reports that an output window for optically pumped terahertz （THz） laser has been fabricated by depositing a capacitive nickel-mesh on a thick high-resistivity silicon substrate （approximating to 5 mm thick）. Unlike the conventional process of depositing a gold film approximating to 100 nm on negative photoresist using electron-beam evaporation, a nickel film approximating to 1.5 μm thick is directly deposited on the clean surface of dielectric substrate using magnetron sputtering and then a positive photoresist is spun onto the nickel metal surface at 6000 r for 60 s. A transmittance spectrum of the output window in a certain frequency range （say, from zero to 1 THz） has been obtained by using THz time domain spectroscopy. Moreover a transmittance spectrum simulated numerically has also been estimated with respect to the output window using the transmission-line model （TLM） containing attenuation component from dielectric substrate. The simulation results show that the TLM can explain well the experimental curve in a certain frequency range from zero to 1 THz. Thus it is demonstrated that the improved optical component can be efficiently used as both output coupler and output window for optically pumped THz lasers.